Quality Regimes in Africa - Shabani, Juma (International Higher Education, 2013)
Since the advent of the knowledge economy society, quality assurance plays a major role in the development and implementation of qualifications frameworks needed in order to promote academic mobility. This article reviews quality assurance initiatives launched at national, sub-regional and regional levels in Africa. It analyzes the results achieved, challenges and opportunities and maps out future prospects. The article also raises a series of research questions that are required to further improve quality assurance in Africa.